Gambaran Penjualan dan Investası Obat Generık Apotek “X” Kelurahan Kampung Satu Tarakan Menggunakan Analısıs ABC Tahun 2022 - Hendriansyah Hendriansyah; Benazir Evita Rukaya; Syuhada Syuhada (Politeknik Kaltara, 2024)
Pharmacies as health facilities and businesses, require good management to avoid shortages or excess stock of medicines. This research aims to optimize generic drug inventory management at pharmacy